The Prognostic Value of the Left Ventricular End Diastolic Volume, Ejection Fraction and the Development of Dyarrhythmia in Ischemic Heart Disease. - Saeed, Basil N. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Study the correlation between the left ventricular end diastolic volume (LVEDV), ejection fraction (EF) and the development of arrhythmia.Patients and methods: Two hundreds patients with documented acute coronary syndrome and myocardial infection with dysrhythmia documented by ECG and holter monitoring assessed at the cardiac department at Baghdad teaching hospital over the period Jan-Dec 2007. These dysrhythmias were corelated with left ventricular end diastolic volume and ejection fraction.Results: The patients were divided into 4 groups according to LVEDD and EF. The 1st group, 40 patients (20%) found to have non sustained ventricular tachycardia was associated with higher LVEDD (62-72mm) and low EF (30-39%) in comparison with other groups. A 2nd group of 80 patients (40%) have occasionally ventricular ectopic, their left ventricular end diastolic dimension is (52-58 mm) and ejection fraction in higher than the 3rd group 10 patients (5%) who had atrial fibrillation were having normal left ventricular end diastolic volume but ejection fraction was 45%. A 4th group of 40 patients (20%) were having occasional atrial ectopic have both normal ejection fraction and left ventricular end diastolic volume, the remaining 30 patients (15%) from the total did not develop any arrhythmia and their left ventricular end diastolic volume and ejection fraction were normal considered an control groups.Conclusion: It was found that the development of arrhythmia is very significantly correlated with the abnormal increased left ventricular end diastolic volume and more lowering of ejection fraction.